MCSE : - Strebe, Matthew (Network Press, 1997)
The coverage spans every aspect of the NT Server course, including installing, configuring, and administering NT Server networks. A test-simulation program, provided on the companion CD, lets you study and review sample test questions, and identify areas requiring further work